Counseling Values ​​in the Thoughts of Ki Hadjar Dewantoro - adiputra, Sofwan; Mujiyati, Mujiyati (JURNAL INOVATIF ILMU PENDIDIKAN, 2024)
The application of innovation and creativity in counseling can help in building the relationship process between the client and the counselor. Researchers try to construct a counseling model by placing cultural values, and indigenous studies as the philosophy of the study concept. One approach that meets these elements is the "Among system." Researchers try to collaborate on the concept of thinking by using an educational approach in the implementation of indigenous counseling services. The study used the Interpretative Phenomenological Analysis (IPA) design, which explores how individuals understand their personal and social worlds through a detailed examination of their lives's experiences. Data analysis was conducted qualitatively, using Coding data analysis. The technique used is to compare and check the degree of trustworthiness of information obtained through different times and tools. Among is a result of Ki Hadjar Dewantoro's thinking, which means opvoeding or paedagogiek, so that intervention through among values, is an intervention based on pedagogical values.